Enhanced dilution step and gravimetric preparation uncertainty for low-amount fraction standard gas mixtures using a newly developed automatic weighing system for a mini cylinder. (1st October 2022) - Kim, Jeong Eun; Lee, Jin Bok; Kim, Jin Seog; Yang, Inseok; Hong, Kiryong
Abstract: The gravimetric method is widely used to prepare standard gas mixtures in gas cylinders. Several dilution steps are required to prepare a low-amount fraction gas mixture, such as at μmol mol −1 level, using the gravimetric method. We have developed a new automatic weighing system (AWS) that is applicable to a mini cylinder (100 mL or less) to reduce the number of dilution steps. The developed mini-AWS is operated by an automatic cylinder exchange mechanism that is similar to the existing AWS. However, the minimum measurable mass was decreased to measure a small amount of target gas; therefore, the gas mixture can be prepared directly at the μmol mol −1 scale. This study evaluated the fundamental performance of the developed mini-AWS, and we gravimetrically prepared several gas mixtures of nominal 100 μmol mol −1 carbon monoxide (CO) in nitrogen (N2 ). The uncertainties of prepared gas mixtures were consistent within 0.1% of the relative expanded uncertainty. They were then compared to the standard gas mixture, which was gravimetrically prepared using the existing AWS. The compared results agreed within their expanded uncertainties ( k = 2).